PERBANDINGAN JUMLAH KOLONI BAKTERI SEBELUM DAN SESUDAH PENGGUNAAN OBAT KUMUR YANG MENGANDUNG CHLORHEXIDINE ANTARA KELOMPOK PEROKOK DAN BUKAN PEROKOK - CHAIRUNNISA .; ANNISA . (JURNAL ILMIAH SIMANTEK, 2021)
Smoking has a high prevalence rate in Indonesia. Around 61.4 million (36.1%) people use tobacco in the form of smoke andwithout smoke. Hazardous ingredients contained in cigarettes can cause vascularity and salivary secretion, causing the toothsurface to become rough and bacteria easily gather. Chlorhexidine is a germicidal mouthwash that can reduce bacteria in themouth. Chlorhexidine is effective in inhibiting the growth of Gram-positive and Gram-negative bacteria that havebacteriostatic (inhibiting bacterial growth) and bactericidal (killing bacteria) working properties. To compare the number ofbacterial colonies before and after the use of mouthwash containing chlorhexidine between smokers and nonsmokers.Research methods: This study uses an experimental method with a pretest and posttest controlled group research design.The analysis used in this study is the Mann-Whitney test. The study showed that the average number of bacterial coloniesbefore using chlorhexidine in the smokers group was more than the nonsmokers group with a p value = 0,000. The numberof bacterial colonies after using chlorhexidine decreased, with the average number of bacterial colonies in the smoker groupmore than the nonsmoker group with a p value of 0.003. There is a difference between the number of bacterial coloniesbefore and after the use of mouthwash containing chlorhexidine between smokers and nonsmokers.